Use of Premixed Parenteral Nutrition during a Phosphate Shortage in a Non-Critically Ill Population - Curtis, Caitlin S. (Nutr Clin Pract, 2015)
BACKGROUND: Drug shortages pose prescribing problems to clinicians. During fiscal year (FY) 2014, an acute shortage of intravenous potassium phosphate (K-Phos IV), a common supplement in parenteral nutrition (PN), prompted the use of premixed instead of individualized PN to conserve K-Phos IV. Here we quantify the K-Phos IV conserved by using premixed PN and the associated cost differences. MATERIALS AND METHODS: Costs of preparing premixed PN vs individualized PN of equivalent composition were calculated for FY 2014 at a single center tertiary care facility. Quantity and cost of K-Phos IV saved was calculated based on the number of premixed PN prescriptions. Costs for FY 2015 were projected based on drug costs from July 2014. RESULTS: During FY 2014, prescribing premixed in lieu of individualized PN conserved 16,440 mmol K-Phos IV but increased cost of PN by $4,080.45. However, increases in K-Phos IV cost at the end of FY 2014 resulted in premixed PN as a relatively less expensive therapy than individualized PN for our institution. Cost savings of $7,092.20 due to use of premixed PN is projected for FY 2015. CONCLUSIONS: Prescribing premixed PN conserves K-Phos IV during shortages, but it increased direct drug spending in non-critically ill patients at our institution during FY 2014. Persistent shortages can drive market costs of K-Phos IV however, necessitating frequent reconsideration of resource utilization.